Sejarah Musik Melayu di Kota Medan, 1970-2000 - Rahmah, Rahmah; Siregar, Syahruddin; Devianty, Rina (Warisan: Journal of History and Cultural Heritage, 2021)
This article discusses the influence of foreign cultures on the existence of Malay music in Medan City in the period 1970-2000. The arrival of various foreign communities in Medan City also brings their original culture. The acculturation of foreign communities with ethnic Malays produces a beautiful blend of cultures. This study uses the historical method in four writing steps, namely; heuristics, verification or criticism, interpretation, and historiography, with a cultural approach. Ethnic Malay as an egalitarian society can accept foreign culture with open arms. The interaction of the Malay people for hundreds with foreign cultures has brought significant changes to their culture. This can be seen from the various musical genres that influence Malay music. In addition, the use of musical instruments from various foreign cultures also enriches the treasures of Malay music. Even though it was influenced a lot from foreign cultures, Malay music still survives and exists today.